A Synthesis of Decision Models for Tool Management in Automated Manufacturing - Gray, Ann E.; Seidmann, Abraham; Stecke, Kathryn E. (Management Science, 1993)
The evidence is clear that a lack of attention to structured tool management has resulted in the poor performance of many manufacturing systems. Plant tooling systems affect product design options, machine loading, job batching, capacity scheduling, and real-time part routing decisions. With increasing automation in manufacturing systems, there is a growing need to integrate tool management more thoroughly into system design, planning and control. This paper critically evaluates various tool management approaches, identifying the operational tradeoffs and analyzing the models developed to address management decisions involving tooling. These decisions range from selecting the optimal machining parameters and the most economic processing rate for a particular operation, to the loading of tools and jobs on machines and the determination of the optimal tool-mix inventories needed for a particular production schedule. We present an integrated conceptual framework for resource planning to examine how tool management issues, depending upon their scope, can be classified into tool-level, machine-level, and system-level concerns. This framework specifies how decisions made at one level constrain those at lower levels, and how information from lower levels feeds back to higher level decisions. The framework structures our critical evaluation of the modeling approaches found in the academic literature and points to promising directions for future research.